Cover Image. (20th May 2019) - Weichert, I.; Romero‐Ortuno, R.; Tolonen, J.; Soe, T.; Lebus, C.; Choudhury, S.; Nadarajah, C. V.; Nanayakkara, P.; Orrù, M.; Di Somma, S.; ,
Abstract : The cover image, by I. Weichert MRCP * et al., is based on the Research Article** Anticholinergic medications in patients admitted with cognitive impairment or falls (AMiCI).The impact of hospital admission on anticholinergic cognitive medication burden. Results of a multicentre observational study, DOI:10.1111/jcpt.12694 .